Identifying priority questions regarding rapid systematic reviews’ methods: protocol for an eDelphi study - Andrea C Tricco; Peter Bragge; Laurenz Langer; Elie A Akl; John Lavis; Tanja Kuchenmüller; Jovana Stojanovic; Sandy Oliver; Simon Bacon; Chiara de Waure; Paula A B Ribeiro; Danielle Pollock; et al. (BMJ Open, 2023)
Introduction Rapid systematic reviews (RRs) have the potential to provide timely information to decision-makers, thus directly impacting healthcare. However, consensus regarding the most efficient approaches to performing RRs and the presence of several unaddressed methodological issues pose challenges. With such a large potential research agenda for RRs, it is unclear what should be prioritised.Objective To elicit a consensus from RR experts and interested parties on what are the most important methodological questions (from the generation of the question to the writing of the report) for the field to address in order to guide the effective and efficient development of RRs.Methods and analysis An eDelphi study will be conducted. Researchers with experience in evidence synthesis and other interested parties (eg, knowledge users, patients, community members, policymaker, industry, journal editors and healthcare providers) will be invited to participate. The following steps will be taken: (1) a core group of experts in evidence synthesis will generate the first list of items based on the available literature; (2) using LimeSurvey, participants will be invited to rate and rank the importance of suggested RR methodological questions. Questions with open format responses will allow for modifications to the wording of items or the addition of new items; (3) three survey rounds will be performed asking participants to re-rate items, with items deemed of low importance being removed at each round; (4) a list of items will be generated with items believed to be of high importance by ≥75% of participants being included and (5) this list will be discussed at an online consensus meeting that will generate a summary document containing the final priority list. Data analysis will be performed using raw numbers, means and frequencies.Ethics and dissemination This study was approved by the Concordia University Human Research Ethics Committee (#30015229). Both traditional, for example, scientific conference presentations and publication in scientific journals, and non-traditional, for example, lay summaries and infographics, knowledge translation products will be created.